Hubungan Antara Shift Kerja, Masa Kerja Dengan Kelelahan Kerja Pada Perawat Daerah Surakarta Saat Pandemi Covid-19 - Mustain mustain; Ikrima Rahmasari; Tri Yuniarti; Muhammad Syaichul Anam; Selvy Azizah (Jurnal Sehat Mandiri, 2022)
The current end of the Covid-19 pandemic cannot be determined. The increasing number of patients in several hospitals has forced nurses to do more care for these patients. This study aims to determine the relationship between work shifts, length of work and work fatigue among nurses in the Surakarta area during the Covid-19 pandemic. This study used a descriptive analytic method with a sample of 30 nurses in Surakarta. The location was chosen because Surakarta has a fairly high rate of increase in cases infected with Covid-19. The data analysis method used is the independent t-test and chi square test. Based on the results of the independent t-test, it has a significance value of 0.025, which means there are differences in working hours before and after the Covid-19 pandemic. Chi-Square test at a value of 0.024 and 0.005 so that the work shift and length of work affect the work fatigue experienced by nurses. The results of the study also stated that there were differences in working hours for nurses. There was a relationship between work shifts and length of work on work fatigue experienced by nurses. It is better for the hospital management to be able to manage working time and rest time as best as possible so that nurses can remain optimal when working.